The Role of Prior Knowledge and Students’ Perceptions in Learning of Biomedical Sciences - Markus Nivala; Jorma Paranko; Hans Gruber; Erno Lehtinen (Springer, 2022)
The present study investigates whether medical students’ prior knowledge and perceptions about basic biomedical sciences predict learning of these topics at early phases of the medical education. Participants (N = 115) were first year medical students at the University of Turku (Finland). The data consisted of a student perception questionnaire, entrance examination results, and the examination scores of the first year preclinical courses. Compared to the students having only education at the upper secondary school level (n = 58), the students with prior university studies in sciences (n = 57) performed better in the first year course examinations. Out of the four entrance examination subtests, only the subtest in biology predicted performance in the first year course examinations. In terms of students’ perceptions, the students rated the courses that dealt with the human body on microscopic or molecular level the least useful and the most difficult. Yet, the perception of usefulness had no effect on examination performance. The results emphasize the role prior knowledge especially in biology has for learning of medicine. Furthermore, the first year medical students seem to value topics that are more closely related to their everyday experiences and, therefore, perhaps less abstract. The courses on cellular and molecular levels were rated notably low with regard to usefulness. The relevance of cellular and molecular biology to medical profession should be communicated more clearly to the students. Furthermore, basic science topics may benefit from a more integrative pedagogical approach in which the biomedical concepts are conceptualized in diagnostic practice.